Customers' reaction to servicescape failure and associated recovery strategy: an exploratory study in the food service industry - Chua, Bee Lia; Othman, Mohhiddin; Boo, Huey Chern; Abdul Karim, Muhammad Shahrim; Ramachandran, Sridar (Penerbit Universiti Teknologi MARA (UiTM) Malaysia, 2009)
The term ‘servicescape’ refers to the physical environment in a service encounter which elicits internal reactions from customers leading to the display of approach or avoidance behaviours. This study examines the effects of servicescape failures on customers’ responses to the associated recovery strategies in the food service industry. Using the critical incident technique (CIT), data on 226 servicescape failures and 287 recovery strategies were collected from 174 informants who had experienced servicescape dissatisfaction and encountered recovery strategies over various types of the food service industry. The content analysis disclosed that cleanliness issues were the most reported problem in the food service industry, followed by design issues, social issues, and functionality issues. Customers exhibited negative reactions to failures, displaying emotional, physiological, and cognitive responses. It is appears that servicescape failures can significantly diminish perceptions of service performance and evoke feelings of dissatisfaction. The results suggest that customers’ recovery effort evaluations are not much influenced by the type of servicescape failures; overall, a combination of prompt action-oriented responses and sincere empathetic-oriented responses is perceived as the most important determinant of recovery effectiveness.